Metabolic syndrome: what changed during last 30 years? - Т. Ф. Татарчук; Т. М. Тутченко; О. В. Перехрестенко; О. О. Калашніков; М. І. Гламазда (Publishing House TRILIST, 2018)
Metabolic syndrome (MS) is a cluster of cardiometabolic factors that are strongly associated with the risk of serious chronic diseases. The prevalence of MS continues to grow, including among children, adolescents and people of active reproductive age. For the sphere of reproductive medicine, the problem of MS is of particular importance not only because of its negative impact on fertility, the frequency of complications of pregnancy and childbirth, but also because of its transgenerative effect on the health of offspring: it is proved that each of the components of the metabolic syndrome is a powerful epigenetic factor. Recent studies have revealed many new facets of the pathogenesis of MS and expanded the range of its etiologic factors beyond the alimentary factors, which determines the possibility of finding new approaches to prevention and treatment of this pathology. The review presents: evolution of diagnostic criteria for MS and reflection of this process in epidemiology and clinical approaches to the disease; epidemiological data on the prevalence of MS in young adults. A brief overview of a large array of scientific research of the last decade on etiology and pathogenesis of MS, in particular the role of adipose tissue dysfunction of visceral, ileofemoral and ectopic depots, causes of the tendency to prevail in one or another adipose tissue depot, new obesity classification, as well as the role of perinatal and epigenetic, ecological (environmental obesogenes, artificial light contamination), composition of intestinal microbiota, state of the sympathetic nervous system, nutritional deficiencies in the development of obesity and MS is provided. The gender differences of pathogenesis and clinical features of MS, as well as the association of MS with dyshormonal and other pathologies (PCOS, hyperprolactinemia, uterine myoma, endometriosis) of female reproductive health are considered.